Preparation and Application of Nickel Electroplating on Copper (Ni/EC) Electrode for Glucose Detection - Muh. Supwatul Hakim; Haryoko Pangestu; Riyanto (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
An electrode of the nickel electroplating on copper (Ni/EC) has been prepared for a simple and low cost glucose sensor in human urine detection. The electrode was prepared by using pure copper (99.9%) with electroplating method in NiSO4 solution. The electrochemical oxidation of Ni/EC electrode was investigated bys using cyclic voltammetry method. Material Ni/EC identification of morphology used Scanning Electron Magnetic (SEM) and Energy Dispersive X-Ray (EDX). The electrochemical reaction of glucose was analyzed by the cyclic voltammetry method in some electrolyte solutions. Calibration curved was constructed and a linear response for glucose concentration at range 0-0.004 M with R2 = 0.992, LOD and LOQ was determined 4.85x10−4 M, 1.6x10−3 respectively. The proposed electrode might open up a new possibility for the determination of glucose concentration in human urine. Its advantages are simple to prepare, low cost analyzing, and excellent results.